Preliminary evaluation of ERS-1 data for studies on the Brazilian Pantanal - Bignelli, Pedro Alberto (1998)
According to research results it is widely accepted that radar data present strong contrasts between land and water bodies, and it is especially suited to areas with significant cloud cover. In this context, the Pantanal environment (Mato Grosso do Sul State) was chosen to evaluate the potential and contribution of radar data to the understanding and mapping of the dynamics of this area. Specific investigations were carried out on known testsites of the Embrapa-CPAP and INPE (Nhecolândia region) aiming at: 1) comparison of the performance of ERS-1 images in relation to TM-Landsat for mapping vegetation and the water-land boundary; and 2) evaluation of the integration of optical and radar data in generating thematic maps of tropical areas for vegetation mapping. The visual analysis of radar data allow excellent discrimination of areas with sandy soils, salt-lakes, and association of aquatic plants, and also, the integrated optical/radar products contribute to the correct identification of vegetation groups and of local geomorphological aspects.